Echocardiographic assessment of radial right ventricular function in heart transplant recipients. (22nd October 2021) - Atzenhoefer, Marc; Jahangir, Arshad; Payne, Abby; Hendawi, Mohamed; Dakwar, Omar; Ali, Mahmoud; Thohan, Vinay; Muthukumar, Lakshmi
Abstract: Aims: Right ventricular (RV) allograft dysfunction is present in half of all heart transplant (HT) recipients. Non‐invasive assessment of RV function in the setting of rejection is not well described. We outline an echocardiographic technique, short‐axis fractional area change (SAXFAC), to evaluate RV function in the HT population and correlate this with the grade of pathologic rejection. Methods and results: We retrospectively reviewed the electronic medical records of 110 people who received a HT between 1 January 2015 and 29 February 2020 and had no evidence of rejection. One hundred eighty‐two transthoracic echocardiograms (TTEs) completed up to 1 year from the date of transplantation were analysed for the target acoustic window, the parasternal mid‐ventricular short‐axis view. Sixty‐one TTEs from 23 healthy transplants were deemed appropriate for SAXFAC determination. Thirty‐three organ recipients with at least grade 1R allograft rejection were also identified, and their TTEs screened for SAXFAC analysis. Two expert readers independently calculated SAXFAC as follows: RV end‐diastolic area minus end‐systolic area divided by end‐diastolic area. Using commercially available software (Epsilon, Ann Arbor, Michigan), we quantified RV radial strain, longitudinal strain, and apical fractional area change (FAC). Twenty‐eight transplant recipients with grade 0R or 1R rejection and nine patients with clinically significant rejection completed the study analysis. SAXFAC demonstrated significant variability in the entire population with an inverse relationship to severity of allograft rejection ( P ≤ 0.01). Radial strain and FAC were also associated with clinically significant rejection ( P ≤ 0.01). Conclusions: Short‐axis fractional area change is a simple two‐dimensional technique to assess RV function in HT recipients and showed no significant inter‐observer variability. In our small, single‐centre, retrospective case series, lower SAXFAC values were associated with clinically significant allograft rejection. The small sample size and infrequent occurrence of rejection make our observations hypothesis‐generating only. We advocate dedicated RV SAXFAC imaging planes be included when assessing allograft function.